An Expanded Analysis of TRI Theory in Explaining the Adoption of the SRIKANDI Application - Ariyanto, Hepy Hefri; Aprianti, Khairani; Putra, Edy Yulianto (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the factors that affect the readiness and willingness of state civil servants to adopt the SRIKANDI Application, which is a digital system in managing archives and correspondence. The researcher used the expanded Technology Readiness Index (TRI) theory to look at the factors that encourage or hinder application users, then analyzed using statistical methods. Using quantitative methods and the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique on survey data of 422 State Civil Apparatus in the Riau Islands Provincial Government. The results of the study show that the driving factors of the technology readiness index have a significant effect on behavioral intentions, organizational commitment has a significant effect on behavioral intentions, and then behavioral intentions have a significant effect on user behavior. Meanwhile, the technological readiness index barrier does not have a significant effect on behavioral intentions, and the conditions that facilitate it do not have a significant effect on behavioral intentions. This study found that there are several factors that can affect employees in using the SRIKANDI Application. Driving factors such as confidence to use technology and the desire to try new things. Conversely, inhibiting factors such as discomfort and insecurity also have a major effect on the intention to use it. In addition, the organization's commitment to provide adequate training and facilities for technology also has a big influence on the intentions and behavior of employees in using the SRIKANDI Application.